DIAGNOSE ERGONÔMICA DO BALCÃO DE ATENDIMENTO DA BIBLIOTECA CENTRAL DA UNIJUÍ - Santana, Jucieli d. A.; Raguzzoni, Aline N.; Rosa, Tamara P.; Costa, Natalia I. d.; Rosa, Simone M. d. (Salão do Conhecimento, 2013)
Resumo